2012
DOI: 10.1002/ece3.335
|View full text |Cite
|
Sign up to set email alerts
|

Canid hybridization: contemporary evolution in human‐modified landscapes

Abstract: Contemporary evolution through human-induced hybridization occurs throughout the taxonomic range. Formerly allopatric species appear especially susceptible to hybridization. Consequently, hybridization is expected to be more common in regions with recent sympatry owing to human activity than in areas of historical range overlap. Coyotes (Canis latrans) and gray wolves (C. lupus) are historically sympatric in western North America. Following European settlement gray wolf range contracted, whereas coyote range e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…In particular, reproductive isolation of coyotes ( Canis latrans ), eastern wolves ( Canis lycaon ), and red wolves ( Canis rufus ) is incomplete, in which gene flow occurs between them via hybridization and introgression, and likely has done so for much of their evolutionary history where their ranges overlapped (Brzeski, DeBiasse, Rabon, Chamberlain, & Taylor, ; Kyle et al., ; Rutledge, Devillard, Boone, Hohenlohe, & White, ; Rutledge, Garroway et al., ). However, agricultural conversion of natural habitats and predator control programs that extirpated wolf populations facilitated coyote range expansion into the historic ranges of eastern wolves and red wolves during the 20th century (McCarley, ; Nowak, ; Rutledge, White, Row, & Patterson, ; Stronen et al., ). Research suggests that limited population growth of wolves caused by excessive anthropogenic mortality was the primary cause facilitating hybridization between the two eastern North American wolf species and coyotes (Benson, Patterson, & Mahoney, ; Bohling & Waits, ; Hinton, Brzeski, Rabon, & Chamberlain, ; Rutledge, White et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, reproductive isolation of coyotes ( Canis latrans ), eastern wolves ( Canis lycaon ), and red wolves ( Canis rufus ) is incomplete, in which gene flow occurs between them via hybridization and introgression, and likely has done so for much of their evolutionary history where their ranges overlapped (Brzeski, DeBiasse, Rabon, Chamberlain, & Taylor, ; Kyle et al., ; Rutledge, Devillard, Boone, Hohenlohe, & White, ; Rutledge, Garroway et al., ). However, agricultural conversion of natural habitats and predator control programs that extirpated wolf populations facilitated coyote range expansion into the historic ranges of eastern wolves and red wolves during the 20th century (McCarley, ; Nowak, ; Rutledge, White, Row, & Patterson, ; Stronen et al., ). Research suggests that limited population growth of wolves caused by excessive anthropogenic mortality was the primary cause facilitating hybridization between the two eastern North American wolf species and coyotes (Benson, Patterson, & Mahoney, ; Bohling & Waits, ; Hinton, Brzeski, Rabon, & Chamberlain, ; Rutledge, White et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Such animals may represent nothing more than isolated oc currences of once-captive wolves or domesticated wolf-dog hybrids (prendergast 1989;Kays and Feranec 2011), particularly as an estimated 300 000 wolf-dog hybrids are kept as companion animals in the united States (Fischer 2003). Complicating the sociopolitical issues surrounding wolf re-establishment has been an unresolved taxonomy (Chambers et al 2012), lack of information on historical distribution of forms (Wilson et al 2003;Rutledge 2010a), and possible contemporary hybridization among wolves, coyotes, and dogs (vonholdt et al 2011;Stronen et al 2012;Monzón et al 2013;Way 2013).…”
Section: Discussionmentioning
confidence: 99%
“…to place the Caraquet wolf in a broader context, we also obtained hair and bone for stable carbon isotope analysis (δ 13 Wolf. In a more recent study using 12 nuclear markers, this animal clustered with Quebec Coyotes (Stronen et al 2012). however, the sample size of eastern Wolves from Algonquin park in Stronen et al (2012) Bone samples were decalcified using 0.5 n hCl at room temperature for 24-48 h. Samples were rinsed with distilled water and then decanted once the mineral portion of the bone was fully dissolved.…”
Section: Stable Isotope Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…When combined with ecological and morphological data, the ATP‐8 technique can provide a relatively rapid and inexpensive way of identifying the distribution of canids with New World and Old World mtDNA. For example, a large male with morphology similar to that of gray wolves, a body mass of 43 kg, and New World mtDNA, was identified in northeastern Québec about 400 km from the nearest reported location of wolves with New World mtDNA (Stronen et al 2012). This study also reported the presence of wolves with New World mtDNA (including a large male with typical gray wolf morphology) in central Saskatchewan, which appears to be the first record in this Canadian province.…”
Section: Management Implicationsmentioning
confidence: 99%